The Integration of Top-down and Bottom-up Inputs to the Striatal Cholinergic Interneurons - Zhang, Yan-Feng; Reynolds, John N.J. (Current Neuropharmacology, 2024)
Background: Cholinergic interneurons (ChIs) are important for learning and memory. They exhibit a multiphasic excitation-pause-rebound response to reward or sensory cues indicating a reward, believed to gate dopamine-dependent learning. Although ChIs receive extensive top-down inputs from the cortex and bottom-up inputs from the thalamus and midbrain, it is unclear which inputs are involved in the development of ChI multiphasic activity. Methods: We used a single-unit recording of putative ChIs (pChIs) in response to cortical and visual stimulation to investigate how top-down and bottom-up inputs regulate the firing pattern of ChIs. Results: We demonstrated that cortical stimulation strongly regulates pChIs, with the maximum firing rate occurring at the peak of the inverted local field potential (iLFP), reflecting maximum cortical stimulation. Pauses in pChIs occurred during the descending phase of iLFP, indicating withdrawal of excitatory cortical input. Visual stimulation induced long pauses in pChIs, but it is unlikely that bottom- up inputs alone induce pauses in behaving animals. Also, the firing pattern of ChIs triggered by visual stimulation did not correlate with the iLFP as it did after cortical stimulation. Top-down and bottom-up inputs independently regulate the firing pattern of ChIs with similar efficacy but notably produce a well-defined pause in ChI firing. Conclusion: This study provides in vivo evidence that the multiphasic ChI response may require both top-down and bottom-up inputs. The findings suggest that the firing pattern of ChIs correlated to the iLFP might be a useful tool for estimating the degree of contribution of top-down and bottom-up inputs in regulating the firing activity of ChIs.
Keywords: pauses